Impacts of COVID-19 Pandemic on Psychological Well-Being of Older Chronic Kidney Disease Patients - Chan, Alex Siu Wing; Ho, Jacqueline Mei Chi; Li, Jane Siu Fan; Tam, Hon Lon; Tang, Patrick Ming Kuen (Frontiers in Medicine, 2021)
COVID-19 pandemic has been a major global issue, its eventual influences on the population welfare, global markets, public security, and everyday activities remain uncertain. Indeed, the pandemic has arisen a significant global threat. Its psychological impact is predicted to be severe and enduring, but the absolute magnitude is still largely unclear. Chronic kidney disease (CKD) is a complication markedly contributes to the mortality of COVID-19 cases, meanwhile several studies have demonstrated the high frequency and seriousness of the COVID-19 in CKD patients receiving dialysis. Importantly, the influence of COVID-19 among CKD patients without dialysis is still largely unexplored. Thus, we systemically summarized how mental health affects the spreading of COVID-19 to virtually worldwide, covering perspectives from several countries across a wide range of fields and clinical contexts. This review aims to provide the latest details and reveal potential concerns on the public health including psychological well-being of the older patients with CKD..